2021
DOI: 10.1016/j.autneu.2021.102793
|View full text |Cite
|
Sign up to set email alerts
|

Acupuncture modulates immunity in sepsis: Toward a science-based protocol

Abstract: Sepsis is a serious medical condition in which immune dysfunction plays a key role. Previous treatments focused on chemotherapy to control immune function; however, a recognized effective compound or treatment has yet to be developed. Recent advances indicate that a neuromodulation approach with nerve stimulation allows developing a therapeutic strategy to control inflammation and improve organ functions in sepsis. As a quick, noninvasive technique of peripheral nerve stimulation, acupuncture has emerged as a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
35
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(36 citation statements)
references
References 98 publications
(152 reference statements)
0
35
0
1
Order By: Relevance
“… 4 Antibiotics and glucocorticoids have major side effects that limit their clinical implications in sepsis. 34 By contrast, acupuncture has minimal side effects and significant therapeutic potential that can provide beneficial effects on sepsis patients. Studies have shown that EA at ST36 acupoint stimulates neurons expressing Prokr2 protein on the sciatic nerve, uploads nerve signals to the central nervous system, thereby stimulating the adrenal glands to release glucocorticoids and dopamine, inhibiting the secretion of cytokines, and controlling systemic inflammation.…”
Section: Discussionmentioning
confidence: 99%
“… 4 Antibiotics and glucocorticoids have major side effects that limit their clinical implications in sepsis. 34 By contrast, acupuncture has minimal side effects and significant therapeutic potential that can provide beneficial effects on sepsis patients. Studies have shown that EA at ST36 acupoint stimulates neurons expressing Prokr2 protein on the sciatic nerve, uploads nerve signals to the central nervous system, thereby stimulating the adrenal glands to release glucocorticoids and dopamine, inhibiting the secretion of cytokines, and controlling systemic inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, acupuncture has shown remarkable results in counteracting inflammation through the vagal and sympathetic nervous systems. For example, EA can reduce sepsis-induced damage to multiple internal organs such as the lung, heart, kidney, liver, and gastrointestinal tract ( 97 ). The mechanism is that EA stimulates peripheral nerves to induce somatic-autonomic reflexes that, in turn, regulate the functions of the corresponding organs.…”
Section: Discussionmentioning
confidence: 99%
“…He et al [ 21 ], pointed out that for COVID-19, acupuncture may be used, and it can play an anti-inflammatory effect by activating the vagus nerve through the cholinergic anti-inflammatory pathway [ 22 ],. In severe inflammation such as in the sepsis stage, evidence in both preclinical studies and clinical trials shows that activating the autonomic nervous system by acupuncture can significantly modulate the immunity, protect the function of internal organs and decrease the fatality rate [ 23 ],. From the perspective of Chinese medicine, current acupuncture treatments were focused on strengthening the kidney and spleen, and adjusting the lung, heart and liver.…”
Section: Discussionmentioning
confidence: 99%